Perencanaan Pajak Reklame oleh Badan Pendapatan Daerah Kabupaten Sumedang pada Tahun 2022 - Geraldin Arintasari; Imanudin Kudus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out about advertising tax planning by the Sumedang Regency Bapenda using the theory of planning steps according to Sondang P. Siagian (2012). Apart from that, it is also to analyze the constraints and obstacles faced in planning Advertisement Tax as well as solutions that can be taken to resolve them. This research uses qualitative research methods with a descriptive approach. Data collection techniques in this research are through literature studies, field studies with observations and interviews, and documentation studies. The results of this research indicate that the Sumedang Regency Bapenda has implemented Advertisement Tax planning well. This can be proven by the Sumedang Regency Bapenda carrying out advertising tax planning in accordance with the theory of planning steps according to Sondang P. Siagian (2012) and in accordance with applicable Standard Operating Procedures. Apart from that, the realization of Advertisement Tax revenues in 2022 has exceeded the set target, namely with a percentage of 103.32%. It's just that the Sumedang Regency Bapenda experienced problems in the data collection process which resulted in there still being data on potential Advertisement Taxpayers who were not registered as Taxpayers until the end of 2022. This was due to several influencing factors such as the limited number of tax management officers, lack of awareness. and Taxpayer compliance regarding taxes, tax officers have difficulty meeting and contacting Taxpayers who are outside the region, and the socialization provided to Taxpayers has not been optimal.